Elephant Train and Federal Building Across Lakes of the Nations, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Fronting on the Lakes of the Nations is the magnificent $1,500,000 Federal Building. In its center is the Colonnade of the States, comprising forty-eight closely grouped 104 foot columns. The world's largest murals cover the front walls -350 feet long by 60 feet high each, and tell the story of the conquest of the West. The Elephant train in foreground is one of the many which convey visitors throughout the grounds, at a speed limited to 8 miles per hour.